EFFECT OF NEUTRAL DETERGENT FIBRE ON FEED INTAKE IN THE ALPACA (Vicugna pacos) - Paredes G., Julio (2014)
The objective of this study was to evaluate the dry matter intake (DMI) and neutraldetergent fibre intake (NDFI) in the alpaca according to various levels of neutral detergentfibre (NDF) in the diet, and to estimate the intake based on NDF content in the diet. Four3-year-old male Huacaya alpacas of 48.6 ± 1.3 kg body weight (BW) were used in a 4x4Latin Square design. Feed was supplied ad libitum twice daily at 08:00 and 16:00 h. Thetreatments, based on oat hay with different proportions of stems and leaves, processedby a grinder at the size of 2 cm and separated by a sieve of 0.4 cm, were: leaves of oat hay(T1), 50% of oat hay and 50% of leaves of oat hay (T2), whole oat hay (T3) and stems ofoat hay (T4), corresponding to 58.24, 61.38, 66.31 and 70.22% of NDF respectively. Theresults showed that increasing the level of NDF in the diet causes a decrease on DMI(p<0.05) and without affecting NDFI. The maximum NDFI was 0.97% BW and 25.6 g/kg0.75.The average NDFI was 0.92 ± 0.06% BW and 24.22 ± 1.62 g/kg0.75. In conclusion, NDF inthe range used in the study affects feed intake in the alpaca.